An Exploration of the Experiences of the Suluk of the Tarekat Naqshbandiyah-Khalidiyah Babussalam (TNKB) in North Sumatra - Muzakkir Syahrul; Amroeni Drajat; Ziaulhaq Hidayat (Universitas Islam Negeri Imam Bonjol Padang, 2025)
This study aims to examine the experience of the suluk ritual and mental health. To achieve this objective, research questions were formulated regarding the nature of the suluk ritual and ethical considerations to determine its relationship with mental health. Qualitative data was collected using Schutz’s phenomenological approach to explore shared and individual experiences within a specific context. The primary data sources in this study were the mursyid, khalifah, and congregation. Data were collected through observation, interviews, and documentation, and analyzed in various stages with the presentation of results. The results of the study indicate that the suluk ritual is a form of spiritual training that requires each member to perform a series of rituals, such as dhikr, muraqabah, tawajuh, and others. To ensure discipline among participants during the ritual, ethical guidelines have been established that require adherence and implementation before, during, and after the process. These ethical guidelines consistently uphold the practices throughout the suluk ritual. Furthermore, the connection between the suluk ritual and mental health is evident through the intersubjective experiences of the participants who perform the ritual, as they acknowledge the changes they undergo—namely, becoming calm and capable of rational thinking. The practice of zikir, which is the main activity of the suluk ritual, has made a significant contribution to shaping the mental health of the participants. Therefore, it can be concluded that the suluk ritual has a positive influence on the development of mental health.